Constraining the mass density of free-floating black holes using razor-thin lensing arcs. Issue 2 (30th November 2018) - Banik, Uddipan; van den Bosch, Frank C; Tremmel, Michael; More, Anupreeta; Despali, Giulia; More, Surhud; Vegetti, Simona; McKean, John P
ABSTRACT: Strong lensing of active galactic nuclei in the radio can result in razor-thin arcs, with a thickness of less than a milliarcsecond, if observed at the resolution achievable with very long baseline interferometry (VLBI). Such razor-thin arcs provide a unique window on the coarseness of the matter distribution between source and observer. In this paper, we investigate to what extent such razor-thin arcs can constrain the number density and mass function of 'free-floating' black holes, defined as black holes that do not, or no longer, reside at the centre of a galaxy. These can be either primordial in origin or arise as by-products of the evolution of supermassive black holes in galactic nuclei. When sufficiently close to the line of sight, free-floating black holes cause kink-like distortions in the arcs, which are detectable by eye in the VLBI images as long as the black hole mass exceeds ∼1000 Solar masses. Using a crude estimate for the detectability of such distortions, we analytically compute constraints on the matter density of free-floating black holes resulting from null-detections of distortions along a realistic, fiducial arc, and find them to be comparable to those from quasar milli-lensing. We also use predictions from a large hydrodynamical simulation for the demographics of free-floating black holes that are not primordial in origin and show that their predicted mass density is roughly four orders of magnitude below the constraints achievable with a single razor-thin arc.